2019
DOI: 10.1002/jbt.22383
|View full text |Cite
|
Sign up to set email alerts
|

Iron(III) and nickel(II) complexes of tetradentate thiosemicarbazones: Synthesis, structure, cytotoxicity, and lipophilicity

Abstract: Eighteen of the iron(III) and nickel(II) complexes with tetradentate thiosemicarbazidato ligands were synthesized and described, by analytical and spectroscopic methods. Two complexes as an example to the iron and nickel centered ones were crystallographically analyzed to confirm the molecular structures. Cytotoxic effects of the complexes on K562 chronic myeloid leukemia cells were determined by 3‐(4,5‐dimethylthiazol‐2‐yl)‐2,5‐diphenyltetrazolium bromide assay. For comparison, human umbilical vein endothelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Previous studies have demonstrated that presence of a methoxy group (–OCH 3 ) in some molecules can significantly increase biological activity, particularly antiproliferative performance. 42,46,72,73 Unsubstituted Ni II -L 1 (with R = H) did not present antiproliferative activity in any of the tested cell lines (IC 50 > 100 μM). In contrast, its methoxy-containing derivative Ni II -L 2 (with R = –OCH 3 ) was the most potent anticancer agent (IC 50 = 3.4–11.3 μM).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Previous studies have demonstrated that presence of a methoxy group (–OCH 3 ) in some molecules can significantly increase biological activity, particularly antiproliferative performance. 42,46,72,73 Unsubstituted Ni II -L 1 (with R = H) did not present antiproliferative activity in any of the tested cell lines (IC 50 > 100 μM). In contrast, its methoxy-containing derivative Ni II -L 2 (with R = –OCH 3 ) was the most potent anticancer agent (IC 50 = 3.4–11.3 μM).…”
Section: Resultsmentioning
confidence: 92%
“…Therefore, it was not possible to establish a clear correlation when including the methoxy group, in agreement with previous reports. 42,46,72,73 More salophen derivatives are required to assess the role played by substituents (R = H or -OCH 3 ) in the aromatic rings and further studies to examine the pathways of action through which these kinds of complexes act.…”
Section: Cell Viability Studymentioning
confidence: 99%
“…However, complex Fe7 bearing 3-methoxy showed remarkable activity against K562 and P3HR1 cells, arising from allyl group (CH 2 -CH CH 2 ) in the sulfur atom like in similar molecules. [59] The 3,5-dichloro substituents did not contribute positively to cytotoxicity.…”
Section: Cytotoxicitymentioning
confidence: 94%
“…In brief, an easily noticeable change was observed in the backbone of the thiosemicarbazone after complex formation as seen in analogous iron centered structures. [41,59,60] The calculated nominal mass for expected structures of Fe7 and Fe8 having the same molecular formula, C 17 H 19 ClFeN 3 O 3 S, is 436 Da; Fe4 bearing propyl group instead of allyl group on Fe7,8 structures is 438 Da. When compared the masses of picked peaks with those of the possible molecular ions for Fe7, Fe8, and Fe4, it was seen that the expected molecular mass peak [M] was recorded at m/z 454.0, 454.9 (for Fe7); 454.1, 454.6 (for Fe8) and 455.4, 457.9 (for Fe4) with NH 4 adduction, [M+NH 4 ], at lowest intensity (relative abundance <5%).…”
Section: Synthesis and Spectroscopic Analysismentioning
confidence: 99%
See 1 more Smart Citation